Assessing the duty to exhaust internal remedies in the South African law - Madebwe, Tinashe Masvimbo (Rhodes University, Faculty of Law, Law, 2007)
Since the incorporation of the separation of powers doctrine into the South African Constitution, the problem has arisen that, each of the three tiers of government, the Executive, the Judiciary and the Legislature, has sought to protect exclusive jurisdiction over matters that fall within what constitutes that tier's own realm of authority. The effects of this are especially apparent in the field of dispute resolution in administrative law. The administration is predominantly the province of the Executive, and to a lesser extent, the Legislature. Thus, the acceptability of judicial review in dispute resolution and generally, the intrusion by the Judiciary in matters of the administration is perennially questioned and challenged by both the Executive and the Legislature. In this context, the duty to exhaust internal remedies assumes a pivotal role. It offers a compromise, by prescribing qualified exclusion of judicial review as a first port of call for dispute resolution while simultaneously entrusting initial dispute resolution to the administration. Often, this approach yields tangible results, but from a constitutional and fundamental rights perspective, the duty to exhaust internal remedies is problematic. Its exclusion of judicial review goes against, not only the right of access to court in section 34 of the Constitution, but also the rule of law, to the extent that the rule of law allows for the challenging, in court, of illegal administrative action as soon as it is taken. This thesis analyses the constitutionality of the duty to exhaust internal remedies in section 7(2) of the Promotion of Administrative Justice Act by assessing the consistency of section 7(2) of the Promotion of Administrative Justice Act with the right of access to court in section 34 of the Constitution. The thesis initially examines the origins and historical development of the duty to exhaust internal remedies in the English law, and the subsequent adoption of the duty to exhaust internal remedies into the South African common law for the purpose of interpreting and comprehending the duty to exhaust internal remedies as it is appears in section 7(2) of the Promotion of Administrative Justice Act. Ultimately, the study focuses on and identifies the deficiencies in the current approach to the question of the constitutionality of section 7(2) of the Promotion of Administrative Justice Act, and offers suggestions on how the law might be developed.
Keywords: Remedies (Law) -- South Africa; Judicial review of administrative acts -- South Africa; Administrative law -- South Africa; Administrative law -- England; Dispute resolution (Law) -- South Africa; Justice, Administration of -- South Africa